A recontextualização do conhecimento científico: os desafios da constituição do conhecimento escolar - Gallian, Cláudia Valentina Assumpção (2009)
`This research consists in an empirical study which considers a mixed method of investigation, associating quantitative and qualitative aspects when approaching the investigation issues. Its theme is the school knowledge of Sciences and its concern is related to the transformations that occur in the official pedagogical discourse, specifically concerning the conceptual level of school knowledge of this subject. By means of the developed discussion, this study aims to give support to a better understanding of the process of constitution of school knowledge of Sciences, as well as to bring some contributions to the discussion concerning the sociological determinants which may have been acting in order to improve or weaken the students and teachers relationship with this kind of knowledge. The research was conducted in a public state school, from 2006 to 2007, in the city of Valinhos, São Paulo state, and it had as investigation sources: (1) The National Curriculum Parameters of Natural Sciences taught in the fourth cycle of Primary School; (2) a Sciences textbook; and (3) one teacher s Sciences classes in the 8th grade of Primary School. The research procedures adopted were the documental analysis and the class observation. The main theoretical-methodological reference used in order to define the methodological and analytical choices is Bernstein s theory, specifically concerning the aspects that occur in the recontextualization process of scientific knowledge for school transmission. Such theoretical reference, unquestionably dense, inculcated an analytical view to the research, configuring a continuous theoretical reflection. The results obtained evidenced the possibility of capturing the recontextualization process by means of the analysis of its constitutive parts and revealed the occurrence of a progressive impoverishment of the conceptual demand level through the process. Such impoverishment happened within the limits of the investigation due to the losses concerning the relevance given to the establishment of the relationships within the Sciences field (intradisciplinarity) and due to the complexity of the scientific competences and contents in the process of teaching/ learning Sciences